2019
DOI: 10.7717/peerj.7939
|View full text |Cite
|
Sign up to set email alerts
|

The effect of external lateral stabilization on the use of foot placement to control mediolateral stability in walking and running

Abstract: It is still unclear how humans control mediolateral (ML) stability in walking and even more so for running. Here, foot placement strategy as a main mechanism to control ML stability was compared between walking and running. Moreover, to verify the role of foot placement as a means to control ML stability in both modes of locomotion, this study investigated the effect of external lateral stabilization on foot placement control. Ten young adults participated in this study. Kinematic data of the trunk (T6) and fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(88 citation statements)
references
References 26 publications
7
50
0
Order By: Relevance
“…However, we found that the control strategy can be relaxed, achieving less tight foot placement control when constraining foot placement at a slow walking speed, whereas at a normal walking speed the degree of foot placement control was upheld. Overall, we can underscore the growing body of literature [3, 7, 8,12,15,16,26] and confirm that the foot placement model as introduced by Wang and Srinivasan [4] reflects an active control strategy, related to mediolateral stability [5].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…However, we found that the control strategy can be relaxed, achieving less tight foot placement control when constraining foot placement at a slow walking speed, whereas at a normal walking speed the degree of foot placement control was upheld. Overall, we can underscore the growing body of literature [3, 7, 8,12,15,16,26] and confirm that the foot placement model as introduced by Wang and Srinivasan [4] reflects an active control strategy, related to mediolateral stability [5].…”
Section: Discussionsupporting
confidence: 74%
“…CoM position and velocity) during the preceding swing phase. The association between foot placement and CoM kinematic state was shown to be less pronounced during walking with external lateral stabilization [ 5 ], which supports the notion that step-by-step foot placement control promotes mediolateral gait stability.…”
Section: Introductionmentioning
confidence: 63%
“…When participants walked with external stabilization, the stability of the gait pattern increased while vestibular-evoked muscle and force responses decreased as compared to normal walking. Both of these results are not entirely surprising since the control of mediolateral motion is aided by the forces generated by the springs 16,17,22 . As a result, there is a reduced reliance on vestibular signals to maintain upright locomotion during stabilized walking.…”
Section: Discussionmentioning
confidence: 84%
“…Similar to the other variables capable of quantifying movements in the AP and ML direction, there is the possibility that they can highlight a new domain of asymmetry separate from the asymmetry footfall asymmetry variables captured by GaitRite. Future research should explore this upper and lower body relationship post-stroke to examine the similarities and differences during gait and determine if added value is obtained [36,37].…”
Section: Discussionmentioning
confidence: 99%